Chromosomal Microarray Analysis Compared With Noninvasive Prenatal Testing in Pregnancies With Abnormal Maternal Serum Screening. Issue 5 (5th May 2022) - Sagi-Dain, Lena; Salzer Sheelo, Liat; Brabbing-Goldstein, Dana; Matar, Reut; Kahana, Sarit; Agmon-Fishman, Ifaat; Klein, Cochava; Gurevitch, Merav; Basel-Salmon, Lina; Maya, Idit
Abstract : After theoretically normal noninvasive prenatal test results, clinically significant microarray findings can be found in 1 of every 50 pregnancies with high-risk maternal serum screening. Abstract : OBJECTIVE: To examine the effect of maternal age on the rate of clinically significant chromosomal microarray analysis results in pregnancies with abnormal maternal serum screening and to establish the residual risk for abnormal microarray findings after omitting noninvasive prenatal testing (NIPT)–detectable aberrations in pregnancies with abnormal maternal serum screening. METHODS: This retrospective study included all chromosomal microarray analysis tests performed in pregnancies with abnormal maternal serum screening and normal ultrasonogram results over the years 2013–2021. The rate of clinically significant (pathogenic and likely pathogenic) chromosomal microarray analysis findings was compared with a local control cohort of 7, 235 pregnancies with normal maternal serum screening and ultrasonogram results, stratified by maternal age. Calculation of residual risk for clinically significant chromosomal microarray analysis results after normal NIPT was performed by omission of common NIPT-detectable anomalies. Systematic review for studies examining the yield of chromosomal microarray analysis in pregnancies with abnormal maternal serum screening was performed from inception to October 2021, with no time or language restrictions. RESULTS: Of the 559 amniocenteses performed due to abnormal maternal serum screening, 21 (3.8%; 95% CI 2.4–5.7%) clinically significant chromosomal microarray analysis results were found. The residual risk for chromosomal microarray analysis aberrations after theoretically normal NIPT was estimated to be 2.0% (95% CI 1.1–3.6%) (1/50) and was significantly higher for women younger than age 35 years with abnormal maternal serum screening, compared with women with low-risk pregnancies. Systematic review yielded six articles encompassing 4, 890 chromosomal microarray analysis results in pregnancies with abnormal maternal serum screening, demonstrating 2.3% residual risk for chromosomal microarray analysis anomalies after theoretically normal NIPT. DISCUSSION: Clinically significant chromosomal microarray analysis findings can be found in 1 of every 50 pregnancies with high-risk maternal serum screening after theoretically normal NIPT, implying that invasive testing and not NIPT should be recommended in such pregnancies. In addition, NIPT use as a first-tier screening modality instead of maternal serum screening would miss pregnancies at increased risk not only for common autosomal trisomies but for additional chromosomal microarray analysis–detectable disorders.